Angular distribution of upwelling artificial light in Europe as observed by Suomi–NPP satellite. (July 2020) - Tong, Kai Pong; Kyba, Christopher C.M.; Heygster, Georg; Kuechly, Helga U.; Notholt, Justus; Kolláth, Zoltán
Highlights: We examined the relationship between incidence angle and radiance values for VIIRS–DNB night light observations. We find that the radiance from rural and suburban increase towards the horizon, whereas inner cities tend to have highest radiance toward the zenith. Asymmetry of emission of artificial light can be observed in suburban areas where more light is observed in the direction of the inner cities, suggesting that scattering of light from cities may play a role in the angular distribution. Abstract: Measuring the angular distribution of upwelling artificial light is important for modeling light pollution, because the direction of emission affects how light propagates in the atmosphere. We characterize the angular distributions of upwelling artificial light for Europe and northern Africa in 2018, based on night time radiance data for clear nights without twilight and moonlight from the VIIRS–DNB sensor on board the Suomi NPP satellite. We find that in general, suburban areas of major cities emit more light at larger zenith angles, whereas the opposite can be seen at the city centers, where the highest radiance is directed upward. The mean numbers of overflights for the year is 83, meaning that there are on average approximately seven suitable overflights per month. Future analysis may consider using moonlight models to compensate for the retrieval of moonlit scenes and analyzing data from different years in order to expand the amount of available data. As the VIIRS–DNB sensor on board the NOAA–20 satellite (launched 2017) has almost the same design, this method can also be extended to the data taken by NOAA–20.